2015
DOI: 10.1177/1076029615607303
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban for Thromboprophylaxis After Fracture-Related Orthopedic Surgery in Routine Clinical Practice

Abstract: These data from routine practice demonstrate that rivaroxaban can provide effective thromboprophylaxis after fracture-related orthopedic surgery of the lower limb with a favorable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…There were no cases of fatal or critical bleeding in either treatment group. 17 Similar findings were observed in a small study comparing edoxaban to enoxaparin, but it is underpowered and can report biased conclusions. 18 In a larger retrospective cohort study, rivaroxaban was shown to be more effective than LMWH in the reduction of symptomatic VTE (4.9 vs. 8.6%, p ¼ 0.008) after lower limb fractures, driven by a difference in distal DVTs, without increasing the risk of bleeding.…”
Section: Risk Of Venous Thromboembolism and Available Evidence On Antsupporting
confidence: 59%
“…There were no cases of fatal or critical bleeding in either treatment group. 17 Similar findings were observed in a small study comparing edoxaban to enoxaparin, but it is underpowered and can report biased conclusions. 18 In a larger retrospective cohort study, rivaroxaban was shown to be more effective than LMWH in the reduction of symptomatic VTE (4.9 vs. 8.6%, p ¼ 0.008) after lower limb fractures, driven by a difference in distal DVTs, without increasing the risk of bleeding.…”
Section: Risk Of Venous Thromboembolism and Available Evidence On Antsupporting
confidence: 59%
“…Regardless of a similar risk factor prevalence in both samples, more cases of thrombosis and bleeding were reported in the enoxaparin group, but the statistical difference was not significant. The higher incidence of thrombotic events in the enoxaparin group was also described in orthopedic studies, suggesting rivaroxaban may be more effective in thromboprophylaxis [ 10 - 11 ]. As opposed to results found in previous research, however, rivaroxaban was not associated with higher bleeding rates [ 4 ].…”
Section: Discussionmentioning
confidence: 85%
“…Rivaroxaban is an oral direct factor Xa inhibitor widely used in the prevention of VTE after major orthopedic surgery. It has been proven to be an effective and safe thromboprophylactic drug when compared to enoxaparin in patients submitted to hip and knee arthroplasty, as well as after below-knee lower-leg fracture surgery [8][9][10][11]. Regarding thromboprophylaxis in medical inpatients, the MAGELLAN trial reported noninferiority of rivaroxaban effectiveness and safety when compared to enoxaparin [4].…”
Section: Introductionmentioning
confidence: 99%
“…A low incidence of wound complications and other adverse events was also observed. Patients with hip/femoral fracture (median age 73 years) who received rivaroxaban had a lower risk of treatment-emergent serious adverse events compared with those receiving SOC (odds ratio 0.26, 95% CI 0.07–0.88), although this effect was less marked in patients with lower-leg fractures (median age 48 years, odds ratio 0.52, 95% CI 0.18–1.47) 49…”
Section: Trauma-related Fracturesmentioning
confidence: 99%
“…Some countries that participated in XAMOS have a wider label that allows the use of rivaroxaban for thromboprophylaxis after lower-limb fracture surgery. An analysis of 790 patients with lower-limb fracture from XAMOS and a XAMOS extension study (XAMOS-Extra) showed that rivaroxaban was associated with a low incidence of symptomatic thromboembolic and bleeding events, either similar to or numerically lower than those seen in patients receiving SOC 49. The overall incidence of symptomatic VTE in the rivaroxaban-treatment group was 0.57%, compared with 1.14% with SOC.…”
Section: Trauma-related Fracturesmentioning
confidence: 99%